The Relationship Between Geopolitical Risk and Credit Default Swap Premium: Evidence from Turkey* - Soyu Yıldırım, Esra; Ilikkan Özgür, Munise (Ekonomika, 2023)
This study investigates the relationship between the geopolitical risk in Turkey arising out of the war and terror incidents happened in the region during the period 2003:01-2020:06 with the CDS premium. A two-step approach is undertaken for this assessment, in which an ARDL limit test and then a time-varying symmetric and asymmetric causality test are applied to study the possible causality vis-a-vis the subperiods. The ARDL limit test does not reject the hypothesis that there is a co-integrated relationship between CDS premium and geopolitical risk index. In addition, the time-varying symmetric and asymmetric test also identifies causality between CDS premium and geopolitical risk, and establishes periods where the latter influences the former variable both in a positive and negative way. In summary, both the ARDL limit test and the time-varying symmetric and asymmetric test deduce a causal relationship between the studied variables.